Analisis Kesalahan Berbahasa Bidang Fonologi pada Youtube Sindonews: Wawancara Eksklusif Prabowo Subianto dari Hobi Hingga Sisi Humanis - Anjani, Ghifara Firdausa Vidi; Romadona, Tantri Galih; Muryati , Sri (Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes phonological language faults present in Prabowo Subiyanto's exclusive conversation with Abraham Silaban on YouTube. The linguistic faults pertain to phonological elements, especially including phoneme deletion, phoneme addition, and phoneme alteration. Data were obtained using a descriptive qualitative methodology, including listening and note-taking approaches. The findings indicate the presence of linguistic errors relating to pronunciation, namely instances of phoneme deletion, phoneme addition, and phoneme alteration. This study finds that phonological pronunciation mistakes are frequently impacted by the speaker's accent and commonly arise in both formal and informal contexts. This study analyzes phonological language faults present in Prabowo Subiyanto's exclusive conversation with Abraham Silaban on YouTube. This research mostly concentrates on phonological elements, particularly with phoneme deletion, phoneme insertion, and phoneme alteration. The methodology employed is descriptive qualitative, using data gathering approaches that involve auditory observation and documentation. The findings indicate the presence of several types of pronunciation faults in language. These mistakes include phoneme deletion, wherein certain sounds are eliminated from a word, compromising intelligibility; phoneme addition, which involves the insertion of extra sounds into a word; and phoneme change, a transformation that alters the original word structure. The primary element affecting these phonological errors is the speaker's accent, which embodies the traits of their location of origin and everyday usage speaking habits. In addition, these pronunciation errors occur both in formal situations, such as interviews, and in informal communication contexts. This study concludes that although phonological errors can be considered as part of language variation, they still need to be considered, especially in formal communication. It is hoped that the results of this research can become a reference for further research in the field of linguistic error checking as well as efforts to improve more effective and professional communication skills.